Population fluctuation and distribution of bemisia tabaci MEAM1 (Hemiptera: Aleyrodidae) in soybean crops - Ferreira Rodrigues, Raimundo Henrique; Silva, Luciana Barboza; Silva, Maria Carolina Faria; Lopes, José Wellington Batista; Araujo Lima, Edivania; Sobreira Barbosa, Ronny; Oliveira Almeida, Lorrana Francisca (Frontiers in Agronomy, 2022)
Studies on the spatiotemporal dynamics of crop pests enable the determination of their colonization pattern and dispersion in the landscape. Geostatistics is an efficient tool to determine the spatial distribution pattern of the pest in the crops and to visualize them in appropriate maps. Analysis of these maps across the crop developmental stages can be a helpful tool in precision agriculture programs. The aim of this study was to determine the spatiotemporal distribution of Bemisia tabaci whitefly adults and nymphs in commercial soybean crops from planting to harvest. Infestation by the whitefly adults and nymphs started between 30 and 50 days after plant emergence. The maximum population density of ten adults per plant and two nymphs per leaf occurred between 90 and 101 days after plant emergence. In Kriging maps, it was possible to observe the distribution pattern for both adults and nymphs. The colonization of soybean plants by B. tabaci may be divided into three stages: beginning infestation (at the outermost parts of the crop), whole area colonization, and dispersion colonization (when the whole crop area is infested). The density of adult insects was positively correlated with rainfall and relative humidity. Wind speed positively affected the dispersion of adult whiteflies. The distribution pattern of B. tabaci in the soybean crop was aggregated. Climatic factors, such as wind speed, increase the dispersion radius of the whitefly in the crop. Contribution to the field.